2019
DOI: 10.1186/s13227-019-0115-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of gene expression during neurogenesis in the sea urchin Lytechinus variegatus

Abstract: BackgroundThe sea urchin is a basal deuterostome that is more closely related to vertebrates than many organisms traditionally used to study neurogenesis. This phylogenetic position means that the sea urchin can provide insights into the evolution of the nervous system by helping resolve which developmental processes are deuterostome innovations, which are innovations in other clades, and which are ancestral. However, the nervous system of echinoderms is one of the least understood of all major metazoan phyla.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 73 publications
3
11
0
Order By: Relevance
“…The present Netrin stripe along the ciliary band seems consistent with a previous in situ report on sea urchin larva by Slota et al [21] that showed the Netrin gene expression site on the circumoral ectoderm side of the ciliary band. The Netrin gene expression site by the ciliary band is reminiscent of the midline ectoderm in vertebrates and invertebrates [42][43][44].…”
Section: Netrin Stripe Along the Ciliary Bandsupporting
confidence: 93%
See 1 more Smart Citation
“…The present Netrin stripe along the ciliary band seems consistent with a previous in situ report on sea urchin larva by Slota et al [21] that showed the Netrin gene expression site on the circumoral ectoderm side of the ciliary band. The Netrin gene expression site by the ciliary band is reminiscent of the midline ectoderm in vertebrates and invertebrates [42][43][44].…”
Section: Netrin Stripe Along the Ciliary Bandsupporting
confidence: 93%
“…A close spatial association of the Netrin stripe with the ciliary band on the larval surface occurred later, by the 2dpf 4aPL stage (Figure 6A,B). The spatial closeness between the Netrin stripe and the DRD1-expressing ciliary band may occur near the early 2aPL stage, and this appears to be in good agreement with Lv-Netrin in situ reports on the circumoral ectoderm along the ciliary band by Slota et al [21]; this will be further discussed later.…”
Section: Netrin Stripe Along the Ciliary Bandsupporting
confidence: 88%
“…[55] Dunn et al 2008). A very recent paper describes the expression of an uncharacterized Dmrt gene in a sea urchin which is exclusively expressed in the foregut ([74] Slota et al 2019). We assume that this Dmrt gene is a likely ortholog of Dmrt93B which could place the origin of its function in mouth/foregut development at the base of the Bilateria.…”
Section: Discussionmentioning
confidence: 99%
“…Apical organ cells express different ion channels that are associated with mechanosensation in vertebrates. For example, cells in the apical organ of sea urchin, Platynereis and cnidarian larvae express ASIC, and/or TRP channels such as NOMPC or TRPV [343][344][345][346]. Whether and how these cells contribute to substrate or flow sensation is yet to be explored.…”
Section: (B) Flow-based Settlementmentioning
confidence: 99%